Oral Disintegrating Tablets of Proton Pump Inhibitors for Chronic Gastroesophageal Reflux Disease: An Update - Gupta, Avani; Akhtar, Juber; Rastogi, KC; Badruddeen; Khan, Mohammad I.; Ahmad, Mohammad (Current Drug Research Reviews, 2023)
Oral disintegrating tablets (ODT) offer an attractive choice for Gastroesophageal Reflux Disease (GERD) patients suffering from dysphagia. In chronic condition, GERD patient suffers from severe erosive esophagitis. Thus patients feel difficulty and pain during swallowing, which results in patient in-compliance toward medication of tablets or capsules- especially in geriatrics and pediatric patients. These symptoms of GERD patients have attracted the formulation scientists in improving the formulation methodology for such patients. Orally disintegrating tablets could increase the therapeutic impact and drug compliance in these patients. The aim of this compilation is to provide a more convenient way to develop an oral disintegrating drug delivery system of proton pump inhibitors in patients suffering from odynophagia, associated with chronic Gastroesophageal Reflux Disease (GERD). Oral disintegrating tablets (ODT), when placed on the tongue, can quickly disintegrate and release the medicament. It later dissolves or disperses in saliva without any additional water. The saliva containing drug can easily be swallowed and descends into the stomach leading to maximum absorption from the mouth, throat, and upper esophagus. The patient compliance and bio-availability of Oral disintegrating tablets (ODT) are high compared to other conventional tablets.
Keywords: oral disintegration